2014
DOI: 10.9790/487x-16450111
|View full text |Cite
|
Sign up to set email alerts
|

Risks Faced and Mitigation Strategies Employed By Small and Medium Enterprises in Nairobi, Kenya

Abstract: The role Small and Medium Enterprises (SMEs) play in an economy cannot be over emphasized in both developed and developing countries and so their existence and survival is a concern not only to the governments but to scholars as well. In Kenya SMEs constitute a very important sector of economy employing majority of citizens. Majority of SMEs started die the same year due to risks, they face among other factors. This study identified capital market, customer relations, operational-economic, global view, and bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Ahmed and Muntaka (2012) discovered that CEOs with internal loci of control outcomes, implement the structures and processes of environmental monitoring to meet the contingencies of their chosen strategies. Several studies (Awino, 2013;Jaoua and Radouche, 2014;Kagwathi, Kamau, Njau, and Kamau, 2014;Kariuki, 2015, Mitchelmore andRowley, 2013;Napoli, 2012;Njoroge and Wario, 2015;Sandada, Pooe, and Dhurup, 2014) revealed that lack of strategic planning was a constraint to SMEs' gaining access to credit to improve business performance. Awino (2013) found SMEs that use strategic planning were more likely to gain access to credit and other financial resources than those that do not, which results in sustainable business performance.…”
Section: Strategic Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmed and Muntaka (2012) discovered that CEOs with internal loci of control outcomes, implement the structures and processes of environmental monitoring to meet the contingencies of their chosen strategies. Several studies (Awino, 2013;Jaoua and Radouche, 2014;Kagwathi, Kamau, Njau, and Kamau, 2014;Kariuki, 2015, Mitchelmore andRowley, 2013;Napoli, 2012;Njoroge and Wario, 2015;Sandada, Pooe, and Dhurup, 2014) revealed that lack of strategic planning was a constraint to SMEs' gaining access to credit to improve business performance. Awino (2013) found SMEs that use strategic planning were more likely to gain access to credit and other financial resources than those that do not, which results in sustainable business performance.…”
Section: Strategic Planningmentioning
confidence: 99%
“…Awino (2013) found SMEs that use strategic planning were more likely to gain access to credit and other financial resources than those that do not, which results in sustainable business performance. Kagwathi et al (2014) revealed that SMEs lack risk mitigation strategies, which affects their credit scores. The authors found that a credit score allows SMEs to access formal credit that matches the risk and performance of the business.…”
Section: Strategic Planningmentioning
confidence: 99%
“…In other words, studies have shown that only very few SMEs remain variable pass the 5 years period mark which is indicative that majority of SME businesses collapse before their 5th year anniversary (Owduri, 2012;Belá s et al, 2014;Afolabi, 2018). Therefore, to ensure business sustainability of SMEs, there is the need for SME owners and managers to develop the ability to correctly identify risks and take appropriate risk management steps to cure the risk (Kagwathi et al, 2014).…”
Section: Risks In Smesmentioning
confidence: 99%
“…The environment in which SME businesses operate, is continually evolving and, as a result, the risks it faces are continually changing hence risk management strategies must be practiced (Idemobi, 2012). A sound system of risk management therefore depends on a thorough and regular risk management strategy which seem to be lacking in the sector (Kagwathi et al, 2014).…”
Section: Risk Management Practices Of Sme Ownersmentioning
confidence: 99%
“…One of the enhancement strategies is frequently training their people so as to make them define hazards and their underlying causes, and in predicting their occurrence, and relevant controlling techniques. Without such trainings, there will be internal inefficiencies (Kagwathi, Kamau, Njau, & Kamau, 2014). The study recommends for the need to have frequent risk management trainings to SME workforce so that they can enhance their competencies in risk planning, risk controlling, and strategic risk initiatives, and eventually link them with their business operations.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%